1984
DOI: 10.1111/j.1476-5381.1984.tb10136.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heart rate on the effects of prenalterol on regional myocardial blood flow and function during coronary stenosis in dogs

Abstract: 1 The effects of prenalterol, a selective 31-adrenoceptor agonist with potent cardiac positive inotropic properties have been investigated on regional myocardial blood flow (RMBF) (microspheres) and contractile function (ultrasonic crystals) during partial circumflex coronary artery stenosis in 8 open-chest anaesthetized dogs. 2 Prenalterol was investigated at two intravenous doses: 5 gg kg-', which increased myocardial contractility (dP/dt max: +29%) more than heart rate (+12%, up to 150 beatsmin-') and 20 j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1987
1987
1989
1989

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Improvement by nipradilol of ischaemic segment function was almost abolished after atrial pacing, with little change in the other haemodynamic variables. These results may be consistent with the view that slowing of heart rate is of importance in the mechanisms related to the restoration of regional function in the ischaemic area distal to a coronary stenosis (Schamhardt et al, 1981;Gross et al, 1984;Berdeaux et al, 1984).…”
Section: Discussionsupporting
confidence: 90%
“…Improvement by nipradilol of ischaemic segment function was almost abolished after atrial pacing, with little change in the other haemodynamic variables. These results may be consistent with the view that slowing of heart rate is of importance in the mechanisms related to the restoration of regional function in the ischaemic area distal to a coronary stenosis (Schamhardt et al, 1981;Gross et al, 1984;Berdeaux et al, 1984).…”
Section: Discussionsupporting
confidence: 90%
“…Nisoldipine might have decreased oxygen demand of the post-stenotic area, although the increase in heart rate suggests an increase in oxygen demand rather than a reduction. Another possibility arises from the investigation of Berdeaux et al (1984) who observed an increase in wall function of severely ischaemic myocardium after a low dose of prenalterol, a ,B-adrenoceptor agonist, causing an increase in heart rate of 15 beats min-1, while after a high dose of prenalterol an increase in heart rate of 40 beats min 1 was accompanied by an unchanged wall function. This suggests that the reflex-mediated increase in sympathetic activity can cause an increase in wall function even in severely ischaemic myocardium, provided that the increase in heart rate is minimal.…”
Section: Discussionmentioning
confidence: 99%